GLOBALIZATION, ENGLISH, AND MY INDIVIDUAL SELF: A Self-Study through Narrative Inquiry - Luthfiah Nissa, - (2021)
Language is fundamental in shaping one's identity. In today's borderless world, how people see, define and position ourselves appear to be, to a varying degree, interconnected to a host of 'globalizing forces', such as English. Drawing on Bhabha's (1994) notion of hybridity and Gomzina's (2012) multilayered cultural identity as theoretical frameworks, this study aims to trace and understand how the exposure to the English language has impacted my sense of self as an individual. The study used my five personal narratives as data which were written prior to writing up this paper. These narratives encompassed my reflections of various 'significant moments' that highlighted my engagement with English. The narratives point to three major themes: (1) being fascinated with English, (2) feeling superior because of English, and (3) expanding the Self through English. After the narratives were analyzed and interpreted using the theories, the analyses of the narratives show that, while initially my exposure to English had led me to a state of ambivalence regarding my identity, it is through English that I finally was able to expand myself and to understand my hybrid identity: English has indeed become a tool for me to re-define myself as an Indonesian. This self-study confirms the idea that there is no one single true way of defining one's cultural identity, as identity is multifaceted and complex and that it is always in the process of 'becoming'.